Hybrid Nanoparticles: Design of Hybrid MnO2‐Polymer‐Lipid Nanoparticles with Tunable Oxygen Generation Rates and Tumor Accumulation for Cancer Treatment (Adv. Funct. Mater. 12/2015). (March 2015) - Gordijo, Claudia R.; Abbasi, Azhar Z.; Amini, Mohammad Ali; Lip, Ho Yin; Maeda, Azusa; Cai, Ping; O'Brien, Peter J.; DaCosta, Ralph S.; Rauth, Andrew M.; Wu, Xiao Yu
Abstract : On page 1858, X. Y. Wu and co‐workers present new hybrid MnO2 nanoparticles with controllable O2 generation rates by tailoring the hydrophobicity and structure of the polymer and lipid‐based carrier system. The nanoparticles preferentially react with endogenous H2 O2 in the tumor providing sustained O2 generation. The nanoparticles are demonstrated to be safe for intravenous administration, show superior tumor accumulation and retention, and are able to decrease tumor hypoxia and regulate the tumor microenvironment for improving cancer treatment. (Illustration by David Liang.)